Contradiction to Neutralization Reactions (London Journal of Research In Science: Natural and Formal, 2024)
This article contradicts Neutralization reactions by considering the real-life examples of the three most common Neutralization Reactions.
Keywords: contradiction; Neutralization Reactions; Gases; Unbalanced Equations